1985
DOI: 10.3109/00016358509046517
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative WHO xylitol field studies in Hungary I. Three-year caries activity in institutionalized children

Abstract: The aim of this 3-year field study was to assess the value of partial substitution of sucrose with peroral xylitol (14-20 g/day) as a caries-preventive measure (X group) in comparison with systemic administration of fluoride (F group) and restorative treatment procedures solely (C group). An F dentifrice was used unsupervised in the X and F groups, the former containing 10% xylitol. The C group used customary, predominantly F-free dentifrices distributed by the local health authorities. The final material cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 19 publications
3
46
1
Order By: Relevance
“…Therefore, the value of the study re sides rather in the confirmation of a cariostatic poten tial of xylitol when used as a sugar substitute under realistic conditions. The magnitude of the apparent effect of sugar substitution was clinically relevant un der the conditions of the present trial and in agree ment with results from similar investigations [Schei nin and Banoczy, 1985]. Therefore, partial substitu tion of sugar with xylitol may be a valuable approach to caries prevention when used in addition to fluoride and regular oral hygiene.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, the value of the study re sides rather in the confirmation of a cariostatic poten tial of xylitol when used as a sugar substitute under realistic conditions. The magnitude of the apparent effect of sugar substitution was clinically relevant un der the conditions of the present trial and in agree ment with results from similar investigations [Schei nin and Banoczy, 1985]. Therefore, partial substitu tion of sugar with xylitol may be a valuable approach to caries prevention when used in addition to fluoride and regular oral hygiene.…”
Section: Discussionsupporting
confidence: 77%
“…The reversals were already reported in the Turku Sugar Studies [Scheinin and Mäkinen, 1975], and they seemed to also appear in this field study. The remineralization effect of xylitol has been reported in several clinical studies [Scheinin and Mäkinen, 1975;Galliunin, 1981;Scheinin et al, 1985;Kandelman et al, 1988;Isokangas et al, 1989;Kandelman and Gagnon, 1990;Mäkinen et al, 1995b] and documented by clinical photographs on advanced dentinal caries lesions by Mäkinen et al [1995b].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the present topic, it may be more relevant to compare the effect of xylitol and fluorides when both have been used in the same study. Accordingly, the WHO field trials in Hungary [66,67] and French Polynesia [65] showed that substitution of xylitol for sugar in confectioneries resulted in more effective caries prevention than in fluoride-using control groups, the percentage differences amounting to 38-45 and 58-62, respectively, in favour of xylitol. The recent mother-child studies showed that maternal use of xylitol gum prevented caries in infants more effectively than topical fluoride varnish treatments [76] .…”
Section: Review Of Caries Trials: Effectiveness and Safety Of Xylitolmentioning
confidence: 99%